THE RELATIONSHIP BETWEEN BODY MASS INDEX AND WAIST CIRCUMFERENCE WITH FASTING BLOOD GLUCOSE IN PRODUCTIVE-AGE WOMEN IN IDAMGAMLAMO VILLAGE - Silulu, Hendrika Eflin; Simak, Valen F; Renteng, Septriani (Jurnal Keperawatan, 2025)
Central obesity and a high body mass index (BMI) are associated with an increased risk of metabolic disorders, such as elevated fasting blood glucose related to insulin resistance. The aim was to analyze the relationship between BMI and waist circumference with fasting blood glucose levels in productive- age women in Idamgamlamo Village. The research design method used a quantitative cross-sectional approach with 112 female respondents aged 18– 59 years who were taken through the total sampling method. Data were obtained from measuring BMI, waist circumference, and fasting blood glucose, then analyzed using the Pearson statistical test for normally distributed data. The results showed that the majority of respondents had central obesity and BMI in the overweight or obese category. The Pearson test showed a significant relationship between BMI and fasting blood glucose levels (r = 0.293; p = 0.02) and between waist circumference and fasting blood glucose levels (r = 0.334; p = 0.01), although the strength of the relationship was weak. In conclusion, BMI and waist circumference were positively correlated with fasting blood glucose levels.